Does clinical experience with dental traumatology impact 2D and 3D radiodiagnostic performance in paediatric dentists? An exploratory study - Gertrude Van Gorp; Marjan Lambrechts; Reinhilde Jacobs; Dominique Declerck (BMC, 2022)
Abstract Background The aim of this study is to evaluate the impact of experience with traumatic dental injuries (TDI) on paediatric dentists' performance and self-assessed confidence when radiodiagnosing traumatic dental injuries (TDI) and to explore whether this is influenced by the imaging technique used (2D versus 3D). Materials and methods Both 2D and 3D radiological images of young anterior permanent teeth having experienced dental trauma were assessed randomly by a panel of paediatric dentists using structured scoring sheets. The impact of level of experience with dental traumatology on radiological detection, identification and interpretation of lesions and on observer's self-assessed confidence was evaluated. Findings were compared to benchmark data deriving from expert consensus of an experienced paediatric endodontologist and dentomaxillofacial radiologist. Results were analysed using generalized linear mixed modelling. Results Overall, observers performed moderately to poor, irrespective of their level of TDI experience and imaging modality used. No proof could be yielded that paediatric dentists with high TDI experience performed better than those with low experience, for any of the outcomes and irrespective of the imaging modality used. When comparing the use of 3D images with 2D images, significantly higher sensitivities for the detection and correct identification of anomalies were observed in the low experienced group (P < 0.05). This was not the case regarding interpretation of the findings. Self-assessed confidence was significantly higher in more experienced dentists, both when using 2D and 3D images (P < 0.05). Conclusion There was no proof that paediatric dentist's higher experience with TDI is associated with better radiodiagnostic performance. Neither could it be proven that the use of Cone Beam Computed Tomography (CBCT) contributes to an improved interpretation of findings, for any experience level. More experienced dentists feel more confident, irrespective of the imaging modality used, but this does not correlate with improved performance. The overall poor performance in image interpretation highlights the importance of teaching and training in both dental radiology and dental traumatology.